STUDENTS’ VISUAL LITERACY DEVELOPMENT IN PRIMARY SCHOOL: THE INFLUENCE OF TEACHERS’ ABILITY TO VISUALIZE EDUCATIONAL INFORMATION - Malykhin, Oleksandr; Aristova, Nataliia; Zahorulko, Maryna; Lipchevska, Inna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
In modern digital society visual content is an integral part of human life. Developing visual literacy strongly which is connected with such soft skills as critical thinking, creative thinking, communicating and collaborating is an important aspect in school education. The research is aimed at demonstrating the dependence of primary school students’ visual literacy on the primary school teachers’ abilities to visualize effectively educational information in the process of teaching. The survey was conducted within the time period of 2019–2023. The team of researchers from Institute of Pedagogy of National Academy of Educational Sciences of Ukraine (Didactics Department) carried out an exploratory study within the primary school system in Ukraine. The total number of respondents consisted of 52 primary school teachers and 415 students. The study finds out that nowadays the primary school teachers’ visualizing educational information skills are not sufficiently developed. Boosting the development of visualizing educational information skills among primary school teachers will be resulted in primary school students’ visual literacy development. Having significant positive effect on primary school students’ visual literacy development the mentioned primary school teachers’ skills guarantee serious positive impact on learning results of primary school students in total.